Relationship between workplace violence and attitudes towards the nursing profession in nursing students: A cross-sectional study in Iran - Raana Jafarizadeh; Abbas Ebadi; Hosein Mohammadi Roshan; Toktam Kianian; Salman Barasteh; Saba Ebrahimloee; Ferdos Pelarak; Soghra Goliroshan; Mohammad Hatami; Malek Soleimani (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Nursing students are at risk of violence. When nursing students encounter violence in clinical environments, their functional abilities and their desire to stay in this profession are impressed. This research determines the relationship between violence in the workplace and the attitude towards the nursing profession (NP) among Iranian nursing students in 2021. MATERIALS AND METHODS: This cross-sectional research was conducted as an online survey in 2021, and 512 nursing students were selected using the convenience method. Data collection tools included a demographic information form, a professional attitude questionnaire, and a workplace violence questionnaire. Chi-square tests, one-way analysis of variance (ANOVA), sample t-test, and multiple regression were used to analyze the data. RESULTS: The average age was 23.19 ± 4.58 years. Students with high violence experiences had a more negative attitude towards the profession (P = 0.000). The perpetrators of violence were mainly hospital employees (52.42). It was followed by patients and companions (45.86) and instructors (43.95). A significant relationship was found between gender (P = 0.03), age (P = 0.00), academic year (P = 0.005), and marital status (P = 0.008) with attitude towards profession. The findings of this research showed that the variables of gender (boy) and age have an inverse effect on the attitude with a predictive power of 37%; however, the attitude towards the profession becomes positive by increasing the academic year. CONCLUSION: This research provides data to nursing schools to develop intervention and prevention strategies to support students in dealing with the experience of violence. Holding related training courses in violence prevention techniques reduces the other party's anger and can help improve the situation.